Milk Flow Rates from bottle nipples used after hospital discharge. Issue 4 (July 2016) - Pados, Britt Frisk; Park, Jinhee; Thoyre, Suzanne M.; Estrem, Hayley; Nix, W. Brant
Abstract: Purpose: To test the milk flow rates and variability in flow rates of bottle nipples used after hospital discharge. Study Design and Methods: Twenty-six nipple types that represented 15 common brands as well as variety in price per nipple and store location sold (e.g., Babies R' Us, Walmart, Dollar Store) were chosen for testing. Ten of each nipple type (n = 260 total) were tested by measuring the amount of infant formula expressed in 1 minute using a breast pump. Mean milk flow rate (mL/min) and coefficient of variation (CV) were calculated. Flow rates of nipples within brand were compared statistically. Results: Milk flow rates varied from 1.68 mL/min for the Avent Natural Newborn Flow to 85.34 mL/min for the Dr. Brown's Standard Y-cut. Variability between nipple types also varied widely, from .03 for the Dr. Brown's Standard Level 3 to .37 for MAM Nipple 1 Slow Flow. Clinical Implications: The extreme range of milk flow rates found may be significant for medically fragile infants being discharged home who are continuing to develop oral feeding skills. The name of the nipple does not provide clear information about the flow rate to guide parents in decision making. Variability in flow rates within nipples of the same type may complicate oral feeding for the medically fragile infant who may not be able to adapt easily to change in flow rates. Both flow rate and variability should be considered when guiding parents to a nipple choice. Abstract : Did you know there are wide variations in nipple flow rates among various brands available for parents to purchase for feeding their babies after discharge from the neonatal intensive care unit? These variations have consequences for feeding safety for small fragile babies. This innovative study evaluated flow rates of multiple nipple brands on the market and explains the implications for practice of their variation.